(untitled) (Third Sector Social Economic Review, 2021)
The purpose of this study can be expressed as creating a work flow model related to the problems faced by the AOCC (Airline Operation Control Center) organization, which manages the operations of the airlines. For this purpose AOCC working in the departments of airlines operating in Turkey 24 employees and five managers with a decision that can be applied in the conversion of the divertor problems with mutual consultation or e-mail method workflow model has been tried to be created. As a result of the research, it can be reported that a work flow model that can be used in general has emerged.